Tingkat Pemahaman Tentang Olahraga Tradisional Di Kelas V Sekolah Dasar Negeri 2 Sidokepung Buduran Sidoarjo - Dimas Ridho Su’udi; Andun Sudijandoko (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
A country that has several aspects of history, culture and traditions that are developing rapidly, one of which is traditional sports games, one of which is Indonesia. Traditional sports are an alternative that is used to find out traditions and customs in traditional sports games that can be passed on to each generation. The aim of this research is to determine the level of understanding of traditional sports in Class V of SDN 2 Sidokepung Buduran Sidoarjo. This is very necessary for students as a form of awareness in recognizing the customs and traditions of the country. The design of this research is quantitative descriptive research and the data collection method is by filling out a questionnaire. The sample for this research was all male students in class V at SDN 2 Sidokepung Buduran Sidoarjo, totaling 57 students. The results of the research show that class V male students are very interested in traditional sports material in physical education at SDN 2 Sidokepung Buduran Sidoarjo, with the most being in the Medium category, there are 30 students or 53%. In detail, the percentage of research results is for the very low category of 6 students or 11%, the low category of 7 students or 12%, the medium category of 30 students or 53%, the good category of 11 students or 19%, the very good category. as many as 7 students or 5%. The conclusion of this research is that the majority of students' level of understanding at SDN 2 Sidokepung Buduran Sidoarjo in sports learning obtained the highest score in the medium category..